2014
DOI: 10.7314/apjcp.2014.15.19.8183
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Level of Retinol and α-Tocopherol Affords Protection Against Oral Cancer in a Multiethnic Population

Abstract: Background: A comparative cross-sectional study involving oral cancer patients and healthy individuals was designed to investigate associations between retinol, α-tocopherol and β-carotene with the risk of oral cancer. Materials and Methods: This study included a total of 240 matched cases and controls where subjects were selected from the Malaysian Oral Cancer Database and Tissue Bank System (MOCDTBS). Retinol, α-tocopherol and β-carotene levels and intake were examined by high-performance liquid chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…This findings is also consistent with the results obtained where serum level of β-carotene among cases (0.106±0.159μg/ml) were lower as compared to controls (0.134±0.131μg/ ml) in which statistical significance was not observed as well (9). More than 85% of all the case and control subjects do not meet the daily Recommended Nutrient Intake (RNI) as provided by the national guideline (11).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This findings is also consistent with the results obtained where serum level of β-carotene among cases (0.106±0.159μg/ml) were lower as compared to controls (0.134±0.131μg/ ml) in which statistical significance was not observed as well (9). More than 85% of all the case and control subjects do not meet the daily Recommended Nutrient Intake (RNI) as provided by the national guideline (11).…”
Section: Discussionsupporting
confidence: 82%
“…Fruits and vegetables are easily oxidized when it is exposed in the air or cooked under heat for a long period of time resulting in depletion of all vitamins and minerals. Foods that are eaten raw are believed to have higher level of antioxidants properties as the constituent of chemical component still remains intact in the plant itself as compared to the foods that have already been cooked as these vitamins may have been destroyed during the process of cooking (9,16). Currently, the mechanism in which β-carotene inhibits or reduces oral cancer risk and progression is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, two case-control studies [9,10] revealed that patients with oral cancer had significantly lower serum levels of the antioxidant vitamins: vitamin A, vitamin E, and βcarotene and noted that antioxidant vitamins could be predictors when monitoring the occurrence of oral cancer [9]. However, not all studies have obtained consistent findings [11,12]. In addition to the antioxidant vitamins A and E, ubiquinone is also a powerful antioxidant in the mitochondria that participates in energy synthesis through the electron transport chain [13], and ubiquinone can regenerate vitamin E to fight free radicals with other antioxidants [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies reported that phytochemicals and nutrients in fruit and vegetables such as vitamins C, E and phenolic compounds can reduce the risk of cancer including glioma by reducing the endogenous formation of N-nitroso compounds [9][10][11][12][13]. Although some studies have considered the effects of individual antioxidants in relation to risk of cancer [14][15][16], dietary total antioxidant capacity (TAC) has been less studied as a contributing factor to cancer risk [17,18]. Dietary total antioxidant capacity has been associated with a reduced risk of mortality [19], endometrial cancer [20], breast cancer [21] myocardial infarction [22] and heart failure [23].…”
Section: Introductionmentioning
confidence: 99%